A Theoretical Analysis of Factors Influencing Students Decision to Use Learning Technologies in the Context of Institutions of Higher Education - Khan, Mohammad Ayub; Omrane, Amina (Advances in Social Sciences Research Journal, 2017)
This paper studies factors influencing student’s decision to use technology to support their learning. The paper describes all those technological options available for students to support learning such as emails, chat rooms, video lectures, blackboard discussions and Power Point Presentations, for example. Then, the paper explains in detail student factors influencing the decision of students whether to use or not to use learning technologies for learning purposes. The paper findings suggest that the factors under study do influence students´ decisions to opt for technology support and means to learn at school. Overall, the pros are much stronger than cons of using technology for learning purposes and that there are certain strategic actions an educational institution can undertake to influence students´ decisions to use all the technological advances and options available for them at school.